Field-induced slow magnetic relaxation in low-spin S = 1/2 mononuclear osmium(v) complexes. Issue 13 (5th March 2020) - Su, Qian-Qian; Fan, Kun; Huang, Xin-Da; Xiang, Jing; Cheng, Shun-Cheung; Ko, Chi-Chiu; Zheng, Li-Min; Kurmoo, Mohamedally; Lau, Tai-Chu
Abstract : Stable low-spin Os(v ) complexes obtained from the photochemical reactions of NO2 -OsN showing slow magnetic relaxation behavior. Abstract : Photochemical reactions of (PPh4 )[Os VI (N)(L )(CN)3 ] (NO2 -OsN ) with piperidine and pyrrolidine afforded two osmium(v ) hydrazido compounds, (PPh4 )[Os V (L )(CN)3 (NNC5 H10 )] ([PPh4 ]1 ) and (PPh4 )[Os V (L )(CN)3 (NNC4 H8 )] ([PPh4 ]2 ), respectively. Their structures consist of isolated, mononuclear distorted octahedral osmium anions that are well-separated from each other by PPh4 + . Their low spin S = 1/2 and L = 1 ground state was confirmed by magnetometry and DFT calculations. Interestingly, both compounds exhibit slow magnetic relaxation under a bias dc-field. These osmium(v ) complexes are potentially useful building-blocks for the construction of molecule-based architectures with interesting magnetic properties. In contrast, the structurally related (PPh4 )[Os III (L )(CN)3 (NH3 )] ([PPh4 ]3 ), which also has a low-spin S = 1/2 ground state but with a different electronic configuration (5d 5 ), does not exhibit slow magnetic relaxation, due to the absence of any orbital moment ( L = 0). Furthermore, the structurally different osmium(v ) hydrazido compound reported by Meyer, [Os V (tpy)(Cl)2 (NNC5 H10 )](PF6 ) (4 [PF6 ]), also does not exhibit slow magnetic relaxation due possibly to a change in magnetic anisotropy from axial for [PPh4 ]1 and [PPh4 ]2 to planar.